A0–C8 - Foo, Jonathan Enze (2015)
A0–C8 is an alternative way of looking at the theoretical principles of three basic elements of the Western music theory—pitch, rhythm and melody. The project uses visual communication as a lens to organise and articulate the technical language of music by rethinking the way it is presented. The narrative structure of a book allows for the weaving together of history and science with modern tunes and facts to provide a holistic albeit non-exhaustive interpretation of music theory. While the project is based of academic content and existing notational systems, it is by no means a critique on pedagogical methods or an attempt to construct a new system of notating music. Instead, A0–C8 seeks to broaden the perspectives of music enthusiasts and educators by offering an approach in communicating music theory in today’s highly visual society.